2024
DOI: 10.3389/fpsyg.2024.1342592
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating mindfulness-integrated cognitive behavior therapy and mindfulness-based cognitive therapy clinically: the why, how, and what of evidence-based practice

Sarah E. B. Francis,
Frances Shawyer,
Bruno A. Cayoun
et al.

Abstract: It is important to be able to differentiate mindfulness-based programs in terms of their model, therapeutic elements, and supporting evidence. This article compares mindfulness-based cognitive therapy (MBCT), developed for relapse prevention in depression, and mindfulness-integrated cognitive behavior therapy (MiCBT), developed for transdiagnostic applications, on: (1) origins, context and theoretical rationale (why), (2) program structure, practice and, professional training (how), and (3) evidence (what). Wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 93 publications
0
2
0
Order By: Relevance
“…Specifically, a study by Jiang et al focused on older people with diabetes and indicated positive outcomes related to mindfulness practices in managing diabetes and improving overall well-being among diabetic older adults 23 . Another study evaluated the effectiveness of a mindfulness program for older adults with type 2 diabetes living in long-term care facilities, showing positive effects of the mindfulness program on emotional well-being and self-regulation in this group 24 Additionally, the study by Li et al in 2023 found that self-regulation interventions for diabetes management in older people and found that interventions led to increased knowledge, attitude, and self-management behavior scores over time in the experimental group 25 . Another study demonstrated that tailored self-management training programs designed for diabetic older adults can lead to significant improvements in self-management behaviors and glycemic control 26 .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Specifically, a study by Jiang et al focused on older people with diabetes and indicated positive outcomes related to mindfulness practices in managing diabetes and improving overall well-being among diabetic older adults 23 . Another study evaluated the effectiveness of a mindfulness program for older adults with type 2 diabetes living in long-term care facilities, showing positive effects of the mindfulness program on emotional well-being and self-regulation in this group 24 Additionally, the study by Li et al in 2023 found that self-regulation interventions for diabetes management in older people and found that interventions led to increased knowledge, attitude, and self-management behavior scores over time in the experimental group 25 . Another study demonstrated that tailored self-management training programs designed for diabetic older adults can lead to significant improvements in self-management behaviors and glycemic control 26 .…”
Section: Introductionmentioning
confidence: 98%
“…To function effectively, the mind needs to be organized and free from disruptions like preoccupied-mind syndrome or cognitive distortions 24 . Mindfulness practices, commonly used in cognitive-behavioral therapy, can help organize and enhance thinking processes by freeing the mind from unhelpful thoughts, ultimately enhancing the capacity for self-regulation 25 . Mindfulness training has been linked to improvements in emotion regulation, executive functions, and neurocognitive control processes, all of which contribute to enhanced self-regulation abilities across various domains of life 26 .…”
Section: Introductionmentioning
confidence: 99%